On the Cauchy Problem for a Viscous Cahn-Hilliard-Oono System with Chemotaxis (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, we are concerned with the well-posedness and largetime behavior of Cauchy problem for viscous Cahn-Hilliard-Oono system withchemotaxis in 3D whole space. By using the pure energy method, standard continuity arguments together with negative Sobolev norm estimates,one proves the global well-posedness and time decay estimates.
Keywords: Viscous Cahn-Hilliard-Oono system; global existence; decay.